The people we meet - Hill, Jessica J., author; Thompson, Debby, advisor; Levy, E. J., advisor; Sagas, Ernesto, committee member (Colorado State University. Libraries, 2015)
This is a story based on trust -- from losing my sense of love and family when my father's infidelity ruined my perception of the perfect American Dream to finding faith and trust in strangers halfway around the world, in Asia. From the woman I met in Thailand who became my mentor and friend, who urged me to go home and marry at my ripe age of 26, to the fatherly man I met on a motorcycle in Vietnam who made me question the silent punishment I'd given my own father for nearly one year, I will finally begin to understand humanity in a different light. Instead of the love many hoped I would find, I will find a different kind. I will find my small-town roots and my father's little girl, but I will find her in the eyes of a grown woman who's trying so hard to be lost.